Evaluation the Western Canal of Al- Ishaqi Irrigation Project (Journal of Engineering, 2023)
The water scarcity that Iraq suffers from and the low irrigation efficiency in irrigation projects, therefore, it was necessary to evaluate the performance of the irrigation system of the western canal for the Ishaqi irrigation project in Salah al-Din Governorate to determine the water management strategies that can be used to improve the irrigation efficiency in the project. The performance of the field irrigation system was evaluated on two fields of different crops and irrigation methods according to the agricultural reality of the study area in the Western canal for the Al-Ishaqi Irrigation Project in Salah Al-Din Governorate. The fieldwork included measurements of the moisture content before and after irrigation, field capacity, and measuring the inflow of each field using a venturi flume to find the discharge inside the field and measuring the depth of the root during the growing season. The field measurements showed that the actual average water application efficiency for field W1, which is irrigated with the Border irrigation system is 36.1%, and in field W2, which is irrigated with the furrow irrigation system is 26.8%. As for the water distribution efficiency, the average distribution efficiency for fields W1 and W2 was about 98.8% and 98.4%, respectively.  Field measurements showed that the actual conveyance efficiency of the western canal is 93.1%.  The overall project efficiency for the western canal was 28.3%. The results of this evaluation conducted in the western canal t revealed that farmers are using more water than required, resulting in a large amount of water loss in the fields by deep permeation observed in this study due to inefficient use, poor irrigation schedule, and lack of knowledge and skills sufficient farmers have in managing water.